Grinding performance and theoretical analysis for a high volume fraction SiCp/Al composite. (April 2022) - Gu, Peng; Zhu, Chuanmin; Mura, Andrea; Maculotti, Giacomo; Goti, Edoardo
Abstract: SiCp/Al composite is widely used in space shuttle slides, automotive and machine tools. In this paper, ground surfaces of SiCp/Al composite, obtained with different grinding process parameters, are characterized in terms of friction and wear performances under dry and lubricated conditions. The wear mechanism of SiCp/Al composite is firstly found the combination of cohesive and abrasive wear, then a method to calculate the wear volume of SiCp/Al composite is proposed, and a comprehensive wear evaluation system of SiCp/Al composite is established, in which the three indicators of friction coefficient, wear depth, and equivalent wear section area are adopted to evaluate usability performance. The prediction models of the wear indicators were established and the errors between the experimental and predicted results are within 7%. Finally, the NSGA-II multi-objective algorithm is used to optimize surface performance of the SiCp/Al composite, and the optimized grinding process parameters are obtained as the wheel speed of 33 m/s, the table speed of 0.4 m/min and the grinding depth of 9 μm.